(untitled) (Texas Journal of Philology, Culture and History, 2022)
This article discusses the problem of studying the fishing and agricultural vocabulary of the northern dialect of the Karakalpak language, as well as in the Turkic languages, in this case, the Karakalpak language. Words related to fishing and farming in the Karakalpak language are presented, with examples of their use in other Turkic languages and differences in their use in the conversations of the northern dialect of the Karakalpak language. The areal of distribution of dialect professional words associated with cattle breeding are also given on the basis of linguistic maps showing the distribution of the population of the northern regions of Karakalpakstan, where the northern dialect regions of the Karakalpak language were calculated.The difference in the use of words related to agriculture in the northern dialect of the Karakalpak language, firstly, creates the possibility of creating dialectological dictionaries based on the division of professional words related to the Karakalpak language into thematic groups, and secondly, the fact that words related to agricultural professions are used in our language today, they are not exaggerated in our literary language, but instead of dialect words, as a result of its use, it is noted that it ensures the activity of the word in society